2017
DOI: 10.1001/jamadermatol.2017.4483
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Monitoring During Systemic Terbinafine Therapy for Pediatric Onychomycosis

Abstract: Dr Adotama and Mr Tinker had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis. Study concept and design: Adotama, Glass, Allen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 3 publications
0
23
0
8
Order By: Relevance
“…The rates of grade 1 and grade 2 ALT and AST measurement elevation, anemia, lymphopenia, and neutropenia for all medications were similar to the baseline rates in our population. Previous studies [4][5][6][7][8][9] have also found low rates of abnormalities. A study by Elewski et al 4 on the safety and efficacy of terbinafine vs griseofulvin in children with tinea capitis found that hematologic and biochemical abnormalities were "infrequent without evidence of drug effect."…”
Section: Discussionmentioning
confidence: 91%
“…The rates of grade 1 and grade 2 ALT and AST measurement elevation, anemia, lymphopenia, and neutropenia for all medications were similar to the baseline rates in our population. Previous studies [4][5][6][7][8][9] have also found low rates of abnormalities. A study by Elewski et al 4 on the safety and efficacy of terbinafine vs griseofulvin in children with tinea capitis found that hematologic and biochemical abnormalities were "infrequent without evidence of drug effect."…”
Section: Discussionmentioning
confidence: 91%
“…Very few clinical trials have been published on the efficacy and safety of onychomycosis treatments in children with preliminary evidence suggesting currently available onychomycosis treatments are effective and appear safe to use in children . Dosing regimens must be readjusted according to the child's weight . As the pharmacokinetics of antifungals are generally different in children versus adults, understanding the adverse effects associated with antifungal medications is an important factor in appropriately managing fungal infections …”
Section: Special Populationsmentioning
confidence: 99%
“…69 Dosing regimens must be readjusted according to the child's weight. 67,70 As the pharmacokinetics of antifungals are generally different in children versus adults, understanding the adverse effects associated with antifungal medications is an important factor in appropriately managing fungal infections. 71,72…”
Section: Childrenmentioning
confidence: 99%
“…Routine4 laboratory monitoring should be considered in any child receiving oral antifungal agents for onychomycosis. [17][18][19] On the contrary, topical therapy has minimal adverse effects and is considered safe.…”
Section: Discussionmentioning
confidence: 99%